Aggressive orbital rhabdomyosarcoma in adulthood: A case report in a public hospital in Damascus, Syria - Tagrid Younes Ahmad (Thieme Medical and Scientific Publishers Pvt. Ltd., 2018)
Orbital rhabdomyosarcoma (RMS) is a highly malignant tumor that originates mainly from mesenchymal tissue. It is considered a rare childhood malignancy; therefore, presentation in adulthood is scarce. In this case report, a 36-year-old male patient presented with a rapidly progressive RMS of the left orbit. The patient was treated in a different institution with radiochemotherapy with good response. However, relapse occurred after 2 months of completing the course, as rapid growing proptosis. Computed tomography scan revealed a lesion in the left orbit with invasion of the left ethmoid cells and the left maxillary sinus. Exenteration of the left orbit with the left partial maxillectomy and ethmoidectomy was performed. RMS is a highly aggressive malignancy that should be considered in any orbital mass that progresses rapidly. Surgery should be the first line in treatment. Delay in diagnosis and inappropriate treatment negatively affects the outcome.